Implementation of Mind Mapping Learning Method Towards Conversation Ability of Non-Formal Elementary School Students in English Learning - Sari, Ratna; Aan Yuliyanto; Rogibah, Rogibah; Yanani, Eka Nengsih Kardiyanti; Nurhaeni, Ai Siti; Abidin, Abidin (International Conference on Elementary Education, 2025)
In the era of globalization, English is regarded as a communication and information access language in addition to being a language for communication.. However, many students have difficulty communicating using English. This literature review aims to find out how Students learning English in non-formal primary schools can benefit from using the mind mapping learning paradigm to improve their conversational abilities. This method uses a branched structure that allows users to organize their minds hierarchically and intuitively. In the context of education, Mind mapping has demonstrated itself to be effective in increasing understanding, creativity, and information retention. Mind mapping facilitates a more active and engaged thought process through colors, images, and keywords so students can more easily associate new information with existing knowledge. The technique also encourages student collaboration and discussion, improving communication and cooperation skills. Previous research shows that students who learn English using the mind-mapping method are superior in their conversation skills compared to students who do not understand English utilizing the mind-mapping method.